2014
DOI: 10.1128/mbio.00025-14
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Penetrates the Brain via Destruction of the Olfactory and Trigeminal Nerves: Implications for the Pathogenesis of Neurological Melioidosis

Abstract: Melioidosis is a potentially fatal disease that is endemic to tropical northern Australia and Southeast Asia, with a mortality rate of 14 to 50%. The bacterium Burkholderia pseudomallei is the causative agent which infects numerous parts of the human body, including the brain, which results in the neurological manifestation of melioidosis. The olfactory nerve constitutes a direct conduit from the nasal cavity into the brain, and we have previously reported that B. pseudomallei can colonize this nerve in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 30 publications
(39 reference statements)
3
73
0
Order By: Relevance
“…During our initial studies in mice, we also demonstrated that B. pseudomallei was present in the brain stem, increasing in number for up to 48 h postinfection, indicating, though not definitively demonstrating, that bacteria may enter via the trigeminal nerve after intranasal inoculation (105). We have now confirmed that B. pseudomallei penetrates the intact respiratory epithelium in mice and migrates along Schwann cell-encased trigeminal nerve bundles to the cranial cavity (326). Figure 4B to D demonstrate B. pseudomallei localized within the branches of the trigeminal nerve.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriasupporting
confidence: 57%
See 3 more Smart Citations
“…During our initial studies in mice, we also demonstrated that B. pseudomallei was present in the brain stem, increasing in number for up to 48 h postinfection, indicating, though not definitively demonstrating, that bacteria may enter via the trigeminal nerve after intranasal inoculation (105). We have now confirmed that B. pseudomallei penetrates the intact respiratory epithelium in mice and migrates along Schwann cell-encased trigeminal nerve bundles to the cranial cavity (326). Figure 4B to D demonstrate B. pseudomallei localized within the branches of the trigeminal nerve.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriasupporting
confidence: 57%
“…The mechanisms by which B. pseudomallei migrates along the olfactory nerves were recently investigated (326). In BALB/c mice, we demonstrated that intranasally delivered B. pseudomallei was associated with widespread crenellation of the olfactory epithelium and loss of the neuron cell bodies.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 91%
See 2 more Smart Citations
“…Such an intra-axonal migration pathway has long been known for neurotropic viruses such as rabies virus, herpesviruses, morbilliviruses, West Nile virus, and poliovirus (45)(46)(47), and also, the bacterium Burkholderia pseudomallei is suspected to migrate along cranial nerves (48). Although, once L. monocytogenes has entered the brain, the intrathecal immune response is intense and develops rapidly, L. monocytogenes is able to efficiently replicate and spread within the brain, causing a progressive and frequently fatal neurological disease (17,29).…”
Section: Discussionmentioning
confidence: 99%